Measuring person-centered integrated care for people living with mild to moderate chronic kidney disease and multimorbidity: a cross-sectional survey - Hecker, Taylor; Jassemi, Sabrina; van Vliet, Liza; Verdin, Nancy; Russon, Nazret; Elliott, Meghan J.; Hemmelgarn, Brenda R.; Santana, Maria J.; Manalili, Kimberly; McBrien, Kerry; Bello, Aminu K.; Quinn, Amity; et al. (Frontiers in Health Services, 2025)
IntroductionPerson-centered integrated care (PC-IC) has been shown to improve health outcomes for individuals with chronic conditions. However, there is limited evidence measuring PC-IC delivery to people with mild to moderate chronic kidney disease and co-morbidities. We aimed to assess PC-IC delivery for this population in Alberta, Canada.MethodsWe conducted a survey (May-December 2023) using the Rainbow Model of Integrated Care Measurement Tool via weblink or telephone to quantify PC-IC using a 5-point Likert agreement scale. Patients with chronic kidney disease (non-dialysis, non-transplant) and co-morbidities, caregivers, and health care providers in Alberta were invited to participate. Participants were recruited through various methods, including in-clinic posters and web-based posts. We assessed responses using descriptive and non-parametric analyses (e.g., Mann–Whitney U-test).ResultsNinety-seven eligible individuals completed the survey; 24 patients, 12 caregivers, and 61 health care providers. Caregivers rated PC-IC significantly lower than patients (overall score: 3.36/5 and 3.91/5, respectively, p < 0.05) and health care providers rated PC-IC moderately (3.56/5). The lowest scored domain was care coordination amongst patients and caregivers (3.43/5 and 3/5, respectively, p < 0.05) and regional health care laws/regulations amongst health care providers (2.94/5).ConclusionSurvey respondents recognized that the overall delivery of PC-IC is not optimal and identified key areas to address including improving care coordination (e.g., communication between providers) and tackling regional health care laws/regulations (e.g., funding models). Our study highlights the need for further exploration regarding why PC-IC is perceived as suboptimal, particularly among subgroups, and how it can be improved.